Subchronic Exposure to Arsenic Represses the TH/TRβ1-CaMK IV Signaling Pathway in Mouse Cerebellum - Huai Guan (International Journal of Molecular Sciences, 2016)
We previously reported that arsenic (As) impaired learning and memory by down-regulating calmodulin-dependent protein kinase IV (CaMK IV) in mouse cerebellum. It has been documented that the thyroid hormone receptor (TR)/retinoid X receptor (RXR) heterodimer and thyroid hormone (TH) may be involved in the regulation of CaMK IV. To investigate whether As affects the TR/RXR heterodimer and TH, we determined As concentration in serum and cerebellum, 3,5,3’-triiodothyronine (T3) and thyroxin (T4) levels in serum, and expression of CaMK IV, TR and RXR in cerebellum of mice exposed to As. Cognition function was examined by the step-down passive avoidance task and Morris water maze (MWM) tests. Morphology of the cerebellum was observed by Hematoxylin-Eosin staining under light microscope. Our results showed that the concentrations of As in the serum and cerebellum of mice both increased with increasing As-exposure level. A significant positive correlation was found between the two processes. Adeficit in learning and memory was found in the exposed mice. Abnormal morphologic changes of Purkinje cells were observed in cerebellum of the exposed mice. Moreover, the cerebellar expressions of CaMK IV protein and the TRβ gene, and TRβ1 protein were significantly lower in As-exposed mice than those in controls. Subchronic exposure to As appears to increase its level in serum and cerebella of mice, impairing learning and memory and down-regulating expression of TRβ1 as well as down-stream CaMK IV. It is also suggested that the increased As may be responsible for down-regulation of TRβ1 and CaMK IV in cerebellum and that the down-regulated TRβ1 may be involved in As-induced impairment of learning and memory via inhibiting CaMK IV and its down-stream pathway.